2021
DOI: 10.1096/fj.202002426rr
|View full text |Cite
|
Sign up to set email alerts
|

Matrix stiffness primes lymphatic tube formation directed by vascular endothelial growth factor‐C

Abstract: Dysfunction of the lymphatic system is associated with a wide range of disease phenotypes. The restoration of dysfunctional lymphatic vessels has been hypothesized as an innovative method to rescue healthy phenotypes in diseased states including neurological conditions, metabolic syndromes, and cardiovascular disease. Compared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 60 publications
(168 reference statements)
0
58
1
Order By: Relevance
“…Changes in ECM composition and matrix stiffness have dynamic effects on vascular signaling (63) and increases in collagen density impaired neovessel length and interconnectivity in an in vitro model of sprouting angiogenesis (64). Similarly, recent evidence has shown that reduced matrix stiffness primes lymphatic endothelial cells to form cord-like structures and increase the expression of lymphatic markers such as LYVE-1 and PROX1 in vitro in response to VEGF-C (65) and promote increased GATA2 expression and GATA2- dependent upregulation of genes involved in cell migration and lymphangiogenesis (66). Notably, we show increased expression of MMP-2 in tissues of the anterior segment of NC- Foxc2 -/- mice ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in ECM composition and matrix stiffness have dynamic effects on vascular signaling (63) and increases in collagen density impaired neovessel length and interconnectivity in an in vitro model of sprouting angiogenesis (64). Similarly, recent evidence has shown that reduced matrix stiffness primes lymphatic endothelial cells to form cord-like structures and increase the expression of lymphatic markers such as LYVE-1 and PROX1 in vitro in response to VEGF-C (65) and promote increased GATA2 expression and GATA2- dependent upregulation of genes involved in cell migration and lymphangiogenesis (66). Notably, we show increased expression of MMP-2 in tissues of the anterior segment of NC- Foxc2 -/- mice ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a stiff extracellular matrix may negatively influence LEC responsiveness to VEGF-C. This is suggested by the ability of soft matrices to increase VEGFR3 expression via GATA2 regulation in LECs [34], and to promote VEGF-C-driven LEC tube formation in hydrogels [128]. Fibrosis and excessive collagen deposition have also been associated with obliteration of lymphatic vessel lumens, thereby contributing to reduced lymphatic function [129].…”
Section: Box 2 Current Treatment Options For Lymphedemamentioning
confidence: 99%
“…In the development of the lymphatic system, ECM stiffness has a strong impact; a soft ECM is essential for lymphatic vessel formation through regulation of GATA Binding Protein 2 (GATA2) and the subsequent downregulation of TGFβ2 [141]. Moreover, it was shown recently that different pathways regulating the formation of lymphatic cord-like structures in an in vitro system can be tuned by different matrix stiffnesses together with VEGF-C concentrations [142].…”
Section: Mechano-transductionmentioning
confidence: 99%